Language planning and policy in Nigeria: the prospects of arabic language - Salisu, Alfa Muhammed; Dollah, Nafi@Hanafi (Journal of Education and Social Sciences, 2015)
Language planning is a deliberate effort to influence the function, structure, or acquisition of languages or language variety within a speech community. It is often associated with government planning, but is also used by a variety of non-governmental organizations, such as grass-roots organizations and even individuals. The goals of language planning differ depending on the nation or organization, but generally, it includes making planning decisions and possibly changes for the benefit of communication. Several efforts are been made to influence the function of Arabic language in Nigeria owing to its long historical antecedents in the country but successive governments have been coming up with different language policies that contribute to the development and decline of the use of Arabic language in Nigeria. This paper attempts to analyze the contribution of language planning to the development and function of Arabic Language in the pre-colonial Nigeria as well as the effect of language planning to the decline of Arabic language in Nigeria recently. Key words: Arabic language, Language planning, Language policy, Nigeria